Child Protection Management in School: Case Study of School Dropouts in North Sulawesi, Indonesia - Umbase, Ruth Sriana; Sanjaya, Dewa Bagus; Mesra, Romi; Kalalo, Griszelda E. (Universitas Pendidikan Ganesha, 2024)
The case of children dropping out of school has become a public concern. Schools are considered less concerned about children's rights. On the other hand, there are still some schools that think that the implementation of the Child Protection Law has increased the workload in schools. However, protecting children's rights in schools creates obligations for educators and education staff. Educators must fulfill children's rights through learning activities and handling children who have problems in the classroom. This research aims to analyze child protection management in schools. The research method used is a case study. The research results show that school child protection management cannot be realized optimally. Educators can carry out learning activities, but handling problematic children must be done more professionally. The school still needs an integrated child protection policy and management document. Child protection in schools is partial - it focuses on fulfilling children's rights to learn according to the Learning Plan. Therefore, the government, society, and the business world must work together to build child-friendly schools, train educators to have managerial skills in protecting children's rights, and handle problematic children to prevent children from dropping out of school and experiencing worse impacts.